Remote meta‐C–H Cyanation of Arenes Enabled by a Pyrimidine‐Based Auxiliary. Issue 41 (6th September 2017) - Bag, Sukdev; Jayarajan, Ramasamy; Dutta, Uttam; Chowdhury, Rajdip; Mondal, Rahul; Maiti, Debabrata
Abstract: An easily removable pyrimidine‐based auxiliary has been employed for the remote meta ‐C−H cyanation of arenes. The scope of this Pd‐catalyzed cyanation reaction using copper(I) cyanide as the cyanating agent was demonstrated with benzylsilanes, benzylsulfonates, benzylphophonates, phenethylsulfonates, and phenethyl ether derivatives. The method was utilized for the synthesis of pharmaceutically valuable precursors. Abstract : One direction : A pyrimidine‐based directing group (DG) was developed for the meta ‐C−H cyanation of arenes using copper(I) cyanide. The broad substrate scope is demonstrated by the use of various different linkers, including silyl, sulfonyl, phosphonate, and ether groups.